Information ethics : - Freeman, Lee A. (Information Science Pub., 2005)
Information Ethics: Privacy and Intellectual Property provides an up-to-date discussion of the main ethical issues that face today's information-intensive society, including the areas of intellectual property rights, privacy, accessibility and censorship. Through chapters written by some of today's leading Information Ethics researchers, this book provides the reader with a thorough overview of the current state of Information Ethics, the dangers and opportunities presented by information technology, and potential solutions to the risks currently faced by today's information society